Adaptations of the evidence-based Transitional Care Model in the U.S. (September 2018) - Naylor, Mary D.; Hirschman, Karen B.; Toles, Mark P.; Jarrín, Olga F.; Shaid, Elizabeth; Pauly, Mark V.
Abstract: Despite a growing body of evidence that adaptations of evidence-based interventions (EBI) are ubiquitous, few studies have examined the nature and rationale for modifications to the components of these interventions. The primary aim of this study was to describe and classify common local adaptations of the Transitional Care Model (TCM), an EBI comprised of 10 components that has been proven in multiple clinical trials to improve the care and outcomes of chronically ill older adults transitioning from hospitals to home. Guided by Stirman's System of Classifying Adaptations, 582 transitional care clinicians in health systems and community-based organizations throughout the U.S. completed a survey between September 2014 and January 2015; interviews were then conducted with a subset of survey respondents (N = 24) between April and December 2015. A total of 342 survey respondents (59%) reported implementation of the TCM in distinct organizations. Of this group, 96% reported a mean of 4.4 adaptations to the 10 TCM components (40%, one to three; 43%, four to six; and 17%, seven to nine). Nine of ten respondents (94%) reported contextual adaptations while content adaptations were less frequently reported (58%). The top three reported adaptations all related to context (i.e., delivering services from hospital to home, relying on advance practice nurses, and fostering care continuity); interviews clarified a diverse set of reasons for such modifications. Findings reinforce the need for investment in adaptation science and suggest hypotheses to guide rigorous examination of the association between adaptations of TCM components and desired outcomes. Highlights: Describes adaptations of an evidence-based intervention (EBI). Advances the case for investment in adaptation science. Reinforces need to achieve balance between fidelity and adaptation. Offers hypotheses to assess effects of an EBI in the health care sector.